Analysis of Community Welfare in the Implementation of the City Minimum Wage: Johns Rawls Justice Approach - Andrean Caspari; Arman Arman; Achmad Nur Wahyu Kartiko; Robertha Astri Karunia Dewi Rizkwanti (Univiversitas Dr. Djar Wattiheluw, 2024)
This study aims to analyze the welfare of the people in Tanjung Pinang City regarding implementing the city's minimum wage using a Critical Study approach, specifically John Rawls' Theory of Justice. Data collection for this research utilizes secondary data sources, including reports, literary books, and other literature sources. The findings suggest that community welfare is crucial for everyone in fulfilling Decent Living Needs (KHL), assessed through various aspects such as health, education, employment, housing, consumption, transportation, income, and expenses, particularly in the context of the Minimum Wage Implementation in Tanjung Pinang City. John Rawls' Justice Approach guarantees freedom for all individuals, including workers and disadvantaged communities. Consequently, the Tanjung Pinang City Government and the private sector assist in the form of training, mentoring, and empowerment for disadvantaged communities and rewards for workers, which include social security, health insurance, and job safety measures provided by companies by the policies implemented by the Tanjung Pinang City Government.